Modelling and simulation of piezoelectric actuator for vibration control - Muhammad, Bashir Bala (2015)
The piezoelectric actuator is a voltage spring system that behaves in similar characteristic to mechanical mass spring system. It converts electrical signal to physical displacement. The displacements profile of the piezoelectric actuator shifts due to hysteresis and creep during actuation. Numerous equations were used to describe model of actuator in the past. In this work, we presented the behaviour of the piezoelectric actuator in terms of mechanical displacement from applied electric potential. The transfer function mathematical model was generated representing the actuator characteristics. The model was developed by system identification from experimental results. A high resolution microscope together with the image processing technique was used to obtain the system characteristics. Simulation using Matlab Simulink was use to validate the experiment. Experimental results specify that displacement of 0.5 µm in length was generated from 25 V and 1.0 µm displacement was obtained from 50 V of input voltage. The model has damping ratio of 0.412. This model can be used to develop the controller for controlling vibration profile. It can also be used for desired micro actuation.